Role of VicRKX and GlnR in pH-Dependent Regulation of the Streptococcus salivarius 57.I Urease Operon - Szu-Chuan Huang (American Society for Microbiology, 2016)
ABSTRACT Ureolysis by Streptococcus salivarius is critical for pH homeostasis of dental plaque and prevention of dental caries. The expression of S. salivarius urease is induced by acidic pH and carbohydrate excess. The differential expression is mainly controlled at the transcriptional level from the promoter 5′ to ureI (pureI). Our previous study demonstrates that CodY represses pureI by binding to a CodY box 5′ to pureI, and the repression is more pronounced in cells grown at pH 7 than in cells grown at pH 5.5. Recent sequence analysis revealed a putative VicR consensus and two GlnR boxes 5′ to the CodY box. The results of DNA affinity precipitation assay, electrophoretic mobility shift assay, and chromatin immunoprecipitation-PCR analysis confirmed that both GlnR and VicR interact with the predicted binding sites in pureI. Isogenic mutant strains (vicRKX null and glnR null) and their derivatives (harboring S. salivariusvicRKX and glnR, respectively) were generated in a recombinant Streptococcus gordonii strain harboring a pureI-chloramphenicol acetyltransferase gene fusion on gtfG to investigate the regulation of VicR and GlnR. The results indicated that GlnR activates, whereas VicR represses, pureI expression. The repression by VicR is more pronounced at pH 7, whereas GlnR is more active at pH 5.5. Furthermore, the VicR box acts as an upstream element to enhance pureI expression in the absence of the cognate regulator. The overall regulation by CodY, VicR, and GlnR in response to pH ensures an optimal expression of urease in S. salivarius when the enzyme is most needed. IMPORTANCE Dental plaque rich in alkali-producing bacteria is less cariogenic, and thus, urease-producing Streptococcus salivarius has been considered as a therapeutic agent for dental caries control. Being one of the few ureolytic microbes in the oral cavity, S. salivarius strain 57.I promotes its competitiveness by mass-producing urease only at acidic growth pH. Here, we demonstrated that the downregulation of the transcription of the ure operon at neutral pH is controlled by a two-component system, VicRKX, whereas the upregulation at acidic pH is mediated by the global transcription regulator of nitrogen metabolism, GlnR. In the absence of VicR-mediated repression, the α subunit of RNA polymerase gains access to interact with the AT-rich sequence within the operator of VicR, leading to further activation of transcription. The overall regulation provides an advantage for S. salivarius to cope with the fluctuation of environmental pH, allowing it to persist in the mouth successfully.